Pengaruh Budaya Organisasi dan Keadilan organisasi terhadap Organizational Citizenship Behavior (OCB) dengan Komitmen Organisasi sebagai Variabel Mediasi - Insan kamil; Harif Amali Rivai (JMK (Jurnal Manajemen dan Kewirausahaan), 2021)
Abstrak This study aims to conduct a test where organizational commitment mediates the influence of organizational culture and organizational justice on organizational citizenship behavior (OCB) studies on employees of PT. Telekomunikasi Indonesia (TELKOM) in the city of Padang, so that it can help PT. Telekomunikasi Indonesia (TELKOM) in Padang City to address OCB issues and organizational commitment. The sampling technique was carried out by saturated sampling which made the entire population as a sample obtained as many as 70 employees. The data analysis used in this study is Smart PLS 3.3 which is useful for finding the influence between variables with mediation. The results of this study are organizational culture, organizational justice and organizational commitment have a positive and significant effect on organizational citizenship behavior (OCB). Keywords : organizational culture, organizational justice, organizational commitment, organizational citizenship behavior (OCB).